Penerapan Arsitektur Perilaku Pada Wadah Sosial Anak Jalanan (Studi Kasus : UPTD Kampung Anak Negeri Wonorejo) - Febrianty, Wiwid Yulia; Yuprapti W, Sri Suryani (Universitas Medan Area, 2025)
Street children are one of the social welfare problems experienced by children and adults. The phenomenon of street children is still often found in big cities, one of which is the city of Surabaya. The government's efforts in dealing with street children through empowerment/training in halfway houses are quite appropriate. The problem that is often encountered in designing is how to create space, mass order and form that is able to become a user container and is able to support the activities of street children in getting coaching activities, learning, developing interests and talents, and proper protection. The behavioral architecture approach in its application always considers the relationship of behavior in design related to architectural design. Architectural design in mediating the occurrence of behavior or vice versa as a deterrent to behavior. This research aims to determine the application of behavioral architecture approach in UPTD Kampung Anak Negeri based on three principles of behavioral architecture. The research method used is qualitative method with data acquisition through literature study. The results of this study explain the successful application of the behavioral architecture approach and the relationship between human behavior, architectural design and the environment at UPTD Kampung Anak Negeri.